(untitled) (Indian Journal of Arid Horticulture, 2025)
A field experiment to study the Effect of organic and inorganic sources of nitrogen on growth, yield and quality of cabbage was conducted at Horticulture Farm, SKN College of Agriculture, Jobner. Results showed that the plant height, plant spread, number of leaves and leaf area increased significantly with the integrated application of nitrogen as compared to control. The highest values for these parameters were recorded with the application of nitrogen 50% through urea + 50% through vermicompost. The yield increased maximally and significantly when nitrogen was supplied as 50% through urea + 50% through vermicompost. It was also recorded that application of 50% nitrogen through urea + 50% nitrogen through vermicompost registered a significant higher values of growth, yield, nitrogen and protein content in leaves of cabbage. However, 50% nitrogen through urea +50% nitrogen through poultry manure was found second most important treatment in increasing the traits under study, which was statistically at par with 50% nitrogen through urea +50% nitrogen through vermicompos.